RESTORATIVE JUSTICE DALAM SISTEM PERADILAN PIDANA INDONESIA: ANTARA NORMA, PRAKTIK, DAN TANTANGAN PENEGAKAN HUKUM - Natalie Simarmata, Dhea; Wildan Awaljon Putra, Muhammad; Krismen, Yudi (STKIP Subang, 2026)
Indonesia’s criminal justice system is undergoing a paradigm shift from a retributive approach toward a restorative approach. Restorative justice has emerged as a response to the shortcomings of the conventional justice system, which is deemed incapable of restoring relationships between offenders, victims, and the community. This study examines how restorative justice is regulated in Indonesian positive law, how it is applied in criminal law enforcement practice, and what obstacles are encountered in its implementation. The research method used is normative legal research with a legislative and conceptual approach. The results of the study indicate that the normative framework for restorative justice in Indonesia remains partial and scattered across various sectoral regulations. Its application in practice faces obstacles in the form of inconsistencies among law enforcement officials, a lack of public understanding, and the absence of a specific and comprehensive law regulating restorative justice. This study concludes that systematic and integrated legal reform is necessary to realize true restorative justice within Indonesia’s criminal justice system.